Analisis Implementasi Sistem Monitoring dan Evaluasi Pada Dinas Sosial Kota Gunungsitoli - Mahatri Gea; Palindungan Lahagu; Syah Abadi Mendrofa; Nanny Artatina Buulolo (Lembaga Pengembangan Kinerja Dosen, 2025)
The development and effectiveness of public services in Indonesia has always been the main concern of the government and society. One important effort in realizing quality public services is through a monitoring and evaluation (M&E) system. Implementation of a monitoring and evaluation system is very important for government agencies. The Gunungsitoli City Social Service is responsible for a number of programs and activities related to social welfare. These programs include social assistance for people in need, social rehabilitation programs, development of street children, protection programs for vulnerable groups such as the elderly or people with disabilities, as well as various other activities aimed at improving social welfare in the city of Gunungsitoli. This research uses a qualitative research approach where qualitative research. The research variable is the Implementation of the Monitoring and Evaluation System. The research was carried out at the Gunungsitoli City Social Service Office which is located at the Government office complex, Dahana Tabaloho, Kec, Gunungsitoli, Gunungsitoli City. Implementation of a monitoring system at the Gunungsitoli City Social Service is a positive step to increase the effectiveness of social programs and community services. There are several points that become conclusions in the analysis of the results of the discussion, namely: the objectives and scope of the monitoring system, limited resources and supporting factors for implementation.